2017
DOI: 10.1038/bmt.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

Against the odds: haplo-cord grafts protect from GvHD and relapse

Abstract: Two competing technologies, haplo-identical transplantation and umbilical cord blood transplantation offer curative treatments for malignant and non-malignant hematologic conditions in patients who lack HLA-identical donors. The choice between the two approaches is mostly driven by comparison of long-term cure rates and frequency of complications. But short-term factors such as ease of implementation, procedural cost and duration of initial admission also affect centers' choices. Haplo-identical transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Non-in vitro T cell depletion for haploidentical grafts and infusion of TNCs at low doses are the key factors for haplo donor chimerism dominance in cord-haplo HSCT. Several factors were identified as correlated with the "winner" graft, including the number and viability of CD34 + cells, HLA matching, and CD3 + cells [14,17,41]. Based on these data, we hypothesized that the number of infused TNCs would predict the "winner" graft.…”
Section: Discussionmentioning
confidence: 99%
“…Non-in vitro T cell depletion for haploidentical grafts and infusion of TNCs at low doses are the key factors for haplo donor chimerism dominance in cord-haplo HSCT. Several factors were identified as correlated with the "winner" graft, including the number and viability of CD34 + cells, HLA matching, and CD3 + cells [14,17,41]. Based on these data, we hypothesized that the number of infused TNCs would predict the "winner" graft.…”
Section: Discussionmentioning
confidence: 99%
“…For those lacking HLA-identical donors, we have used haplo-cord transplants in which definitive hematopoiesis is established by the cord blood graft. 44 , 45 , 46 , 47 , 48 , 49 Engraftment is rapid, GRFS (GVHD and Relapse Free Survival) superior to either haplo-transplant with post-transplant cyclophosphamide and double umbilical cord blood transplantation. 47 , 50 .…”
Section: Introductionmentioning
confidence: 99%
“…21 In comparison with haplo-identical transplant with post-transplant cyclophosphamide, Kwon et al reported that haplo-cord transplant had faster neutrophil recovery, similar survival rates and lower rates of acute and chronic GVHD. 22, 23 Here we report our experience with haplo-cord transplant for high-risk or relapsed and/or refractory lymphoma/CLL patients.…”
Section: Introductionmentioning
confidence: 97%